THE RELATIONSHIP BETWEEN DISASTER MITIGATION KNOWLEDGE AND WORKERS PREPAREDNESS AT NAMORAMBE PUBLIC HEALTH CENTER IN 2025 - Anggita, Rizliana; Br Ginting, efvy Septriani; Giawa, Indah Oktaviana (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Indonesia is a country prone to various types of natural disasters, including floods and landslides that frequently occur in North Sumatra, including Namorambe. The preparedness of health workers is an important aspect in reducing the impact of disasters, which is influenced by their level of knowledge on disaster mitigation. This study aims to determine the relationship between disaster mitigation knowledge and worker preparedness at the Namorambe Community Health Center in 2025. This study uses a quantitative approach with a cross-sectional study design. The population in this study were all health workers at the Namorambe Community Health Center with a sample size of 88 people. Data collection techniques were carried out through questionnaires that had been tested for validity and reliability. Data were analyzed univariately and bivariately using the Chi-square test. The results showed that most respondents had a good level of disaster mitigation knowledge. There was a significant relationship between disaster mitigation knowledge and worker preparedness (p < 0.05), which means that the higher the knowledge, the better the preparedness in facing disasters. These results conclude that there is a significant relationship between disaster mitigation knowledge and worker preparedness at the Namorambe Community Health Center. Increased training and regular outreach on disaster mitigation are needed to enhance the preparedness of healthcare workers.